PENGARUH CELEBRITY ENDORSER TERHADAP PURCHASE INTENTION PADA IKLAN PRODUK MAKANAN - Christopher Santoso; Dewi Mustikasari Immanuel (Universitas Ciputra Surabaya, 2021)
This study aims to analyze the influence of celebrity endorsers on customers’ attitude toward brand, as well as the influence of customers' attitude toward brand on customers’ purchase intention in food product advertisements. This study uses descriptive quantitative research methods using nonprobability sampling technique. Data collection in this study was conducted using a questionnaire in the form of a google form and distributed to 385 respondents who are active users of Instagram in Indonesia, with an age range of 18 years to 34 years who have seen food advertisements delivered by a celebrity endorser on Instagram. This study used a Likert scale instrument with a scale of 1 to 4, and data were analyzed using Partial Least Square (PLS) with SmartPLS software. The results of this study indicate that the variables of trustworthiness, expertise and match-up congruence have a positive and significant effect on purchase intention.